Systemic hemodynamic atherothrombotic syndrome: is it the cause of non-stenosing coronary artery disease in the young? Systemic hemodynamic a atherothrombotic syndrome: is it the cause of non-stenosing coronary artery disease in the young? - Rodríguez Castillo, Arnaldo Alfonso (2022)
Not applicable